1998
DOI: 10.1557/jmr.1998.0324
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and reactivity of tungsten oxynitride

Abstract: High surface area tungsten oxynitride has been prepared by the temperature programmed reaction (TPR) of WO 3 with NH 3 . All samples were characterized by x-ray diffraction (XRD), nitrogen physisorption, CO chemisorption, and elemental analysis. Samples were prepared at different heating rates (b), and a Redhead analysis yielded an activation energy for nitridation of 109 kJ mol 21 . A heating rate of 0.016 K s 21 gave optimal synthesis conditions. Solid state intermediates were studied by interrupting the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Tungsten oxynitride was synthesized by a temperatureprogrammed reduction of tungsten (VI) oxide (Fluka, 95410) in NH 3 atmosphere [35]. Half a gram of WO 3 was loaded in an alumina crucible and placed in a conventional tube furnace (Tetlow Kilns & Furnaces Pty Ltd, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…Tungsten oxynitride was synthesized by a temperatureprogrammed reduction of tungsten (VI) oxide (Fluka, 95410) in NH 3 atmosphere [35]. Half a gram of WO 3 was loaded in an alumina crucible and placed in a conventional tube furnace (Tetlow Kilns & Furnaces Pty Ltd, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…The energetically most favored adsorption site is the threefold C vacancy hollow site (V C /V C ) on the Mo-terminated surface, and the threefold C hollow site (H C /H C ) is the most stable adsorption site on the C-terminated surface. The adsorption energies in Tables 1 and 2 show that the molecular O 2 adsorbs dissociatively on the Mo-terminated surface more easily than on the C-terminated surface, which indicates that Mo-terminated surface is more active [11][12][13][14][15][16].…”
Section: O 2 Adsorption Onmentioning
confidence: 99%
“…In practical applications, the utility of these materials ranges from wear-resistant coatings to superconductors and heterogeneous catalysts [11]. Furthermore, they have potential applications in hydrodenitrogenation (HDN) [12,13] and hydrodesulfurization (HDS) [14,15] processes. Recent studies indicated that molybdenum sulfide under reaction conditions is partially transformed into carbide (MoC x S 2Àx ) where the HDS reactions occur [16].…”
Section: Introductionmentioning
confidence: 99%
“…Haines et al [24] proposed an eclipsed configuration with a Mo-C-Mo-C stacking where half of the C atoms in the second layer and half of the C atoms in the fourth layer are removed is most likely candidate for ␤-Mo2C structure. Mo-terminated surface is very important for catalytic activity and the catalytic reactions occur mainly on it [25][26][27][28]. Previous results for the H adsorption on this surface indicated that H adsorbs more strongly to the metal-terminated carbide surface than to the C-terminated surface [23].…”
Section: Introductionmentioning
confidence: 97%